Lipid-based nano-formulation platform for eplerenone oral delivery as a potential treatment of chronic central serous chorioretinopathy: in-vitro optimization and ex-vivo assessment - Eman Abdelhakeem; Mohamed El-Nabarawi; Rehab Shamma (Taylor & Francis Group, 2021)
Purpose Eplerenone (EPL) is a selective mineralocorticoid receptor antagonist used for treatment of chronic central serous chorioretinopathy which characterized by accumulation of subretinal fluid causing a localized area of retinal detachment. unfortunately, EPL suffers from poor oral bioavailability due to poor aqueous solubility in addition to high hepatic first pass metabolism. Method Aiming to improve its oral bioavailability, EPL-loaded nanostructured lipid carriers (NLCs) were prepared by the emulsification solvent evaporation method and in-vitro evaluated for particle size (PS), polydispersity index (PDI), zeta potential (ZP), and entrapment efficiency (EE%). A D-optimal design was used for study the effect of liquid lipid to solid lipid ratio, surfactant type and percentage on PS, PDI, EE%, and for data optimization. The optimized EPL-loaded NLCs system was further evaluated using in-vitro drug release and ex-vivo permeation studies through rabbit intestine in comparison to EPL aqueous suspension. The physicochemical properties of the drug in the optimized system were further examined using FT-IR and X-ray diffraction studies. Results The resultant NLCs showed small PS (100.85-346.60 nm), homogenous distribution (0.173-0.624), negatively charged particles (ZP −20.20 to −36.75 mV), in addition to EE% (34.31-70.64%). The optimized EPL-loaded NLCs system with a desirability value of 0.905 was suggested through the Design expert® software, containing liquid to solid lipid ratio (2:1) in presence of 0.43%w/v Pluronic® F127 as a surfactant. The optimized EPL-loaded NLCs system showed a PS of 134 nm and PDI of 0.31, in addition to high EE% (76 ± 6.56%w/w), and ZP (-32.37 mV). The ex-vivo permeation study showed two-fold higher drug permeation through rabbit intestine compared to that from the aqueous drug suspension after 24 h, confirming the ability of optimized EPL-loaded NLCs system as successful oral targeting delivery carrier. Conclusion Our results pave the way for a new oral nanotherapeutic approach toward CSCR treatment. In-vivo study is currently under investigation.